IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PAI DI KELAS I SD ALAM BENGAWAN SOLO - Abdurrahman, Muhammad; Muharom, Fauzi (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
The implementation of the Merdeka Curriculum still has obstacles in its implementation. Not a few teaching staff find it difficult to understand, apply and evaluate this new curriculum. So here teachers are expected to be able to adapt quickly and precisely. Remembering that teachers have an important role in the success of teaching and learning activities. This research aims to determine the implementation of the Merdeka Curriculum in Islamic Education Learning in class I at SD Alam Bengawan Solo. This type of research uses qualitative with descriptive methods. The subjects of this research were PAI teachers and class I students at SD Alam Bengawan Solo. Meanwhile, the informants for this research were the school principal and deputy principal for the curriculum department. The research results show that the implementation of the Merdeka curriculum begins with (1) Preparing teaching tools including analysis of CP, TP, ATP, teaching modules and teaching materials. (2) The implementation of learning begins with a diagnostic assessment and learning activities consist of introduction, core and conclusion. (3) Formative and summative assessments.